Gamifying education for classroom engagement in primary schools - Md Rosli Ismail; Tengku Shahrom Tengku Shahdan; Rita Wong Mee Mee; Yugeshineey Subba Rao; Lim Seong Pek; Khatipah Abd Ghani; Wong Yee Von (International Journal of Evaluation and Research in Education (IJERE), 2022)
Gamification carries the element of fun and creativity into classroom teaching. It is not an unusual fact that playing games varied among learners and created an effective classroom environment. In the 21st-century teaching era, learners’ fun and creative learning environment are prioritized. Lessons filled with fun games are believed to produce a positive outcome during a lesson. Therefore, gamification prepares learners to be active and take responsibility for their learning. This study aimed to explore learners’ comprehension of the term ‘gamification’ and the effects of gamified elements implemented in the lesson on the targeted learners. A set of questionnaires was administered through an online survey to 100 respondents from local primary schools around Selangor who took part in a service-learning programmed. The data was then analyzed and presented in the form of tables. Results showed that respondents had prior knowledge of the term ‘gamification’ and the game culture’s overall context. The respondents agreed that their respective teachers had implemented several game elements when conducting a gamified lesson. Results also indicated that respondents were in preference to learn using gamified learning activities that helped them learn subconsciously.